Comments on the percentage of occurrence methodology used in "a study of L band scintillations during the initial phase of rising solar activity at an Indian low latitude station" by H J Tanna, S P Karia and K N Pathak. Issue 3 (1st February 2019) - Paul, B.; De, B.K.; Guha, A.
Abstract: Following Tanna et al. (2013), we computed the percentage of occurrence of S4 index for the period of 2012–2015 using the data of the dual frequency GPS receiver at the Tripura University, Agartala station (23.76°N, 91.26°E) situated at the northern crest of the equatorial ionization anomaly (EIA) region of the Indian Subcontinent. We have observed discrepancy in the results contradicting the actual scintillation occurrence. The distinctly noticeable discrepancy is that the maximum occurrence month is shifted to April 2013 instead of March 2014. The problem arises due to the denominator term used in the percentage of occurrence ratio i.e. the total number of days of observed scintillation activity during the complete period under consideration. But the conventional percentage of occurrence methodology uses the number of days of observation (the total number of days for which data is available) during each month in the denominator. It correctly assigns the maximum occurrence to March 2014 instead of April 2013 and the obtained monthly statistics follow the solar activity during this period.